Echocardiographic assessment of right ventricular contractile reserve in patients with pulmonary hypertension - Ana Rita Almeida; Maria José Loureiro; Liliana Lopes; Carlos Cotrim; Luís Lopes; Débora Repolho; Hélder Pereira (Revista Portuguesa de Cardiologia, 2014)
Introduction and Aim: Right ventricular function is a major determinant of prognosis in pulmonary hypertension. The aim of this study was to assess and compare right ventricular contractile reserve in healthy subjects (controls) and in subjects with pulmonary hypertension (cases). Methods: In this prospective study of seven cases and seven controls undergoing treadmill stress echocardiography, right ventricular S-wave velocity, tricuspid annular plane systolic excursion (TAPSE), right ventricular fractional area change (RVFAC) and stroke volume index were assessed at rest and with exercise. The increase in each parameter between rest and exercise for cases and controls was analyzed and the magnitude of change in each parameter with exercise between cases and controls was compared. Results: A significant increase in S-wave velocity was observed in cases (rest: 9.4±3.1; exercise: 13.7±4.8 cm/s [p<0.05]). In controls there was a statistically significant increase in S-wave velocity (12.9±2.3 to 23.0±7.2 cm/s [p<0.005]), TAPSE (25.7±2.4 to 31.0±3.5 mm [p<0.05]) and RVFAC (53.8±14.7% to 64.4±9.9% [p<0.005]). The magnitude of change in S-wave velocity (cases: 4.3±3.3; controls: 10.1±5.5 cm/s [p<0.05]), TAPSE (cases: 0.6±2.5; controls: 5.3±3.8 mm [p<0.05]) and RVFAC (cases: −0.4±11.8; controls: 10.6±5.9% [p<0.05]) was significantly different between cases and controls. Conclusions: S-wave velocity, TAPSE and RVFAC increased significantly with exercise in controls. S-wave velocity was the only parameter that showed a significant increase in cases, although the magnitude of this increase was significantly less than in controls. Resumo: Introdução e objetivo: A função ventricular direita é um determinante major do prognóstico na hipertensão pulmonar. Caracterização e comparação da reserva contrátil do ventrículo direito em indivíduos saudáveis (controlos) e doentes com hipertensão pulmonar (casos). Métodos: Estudo prospetivo de sete casos e sete controlos submetidos a ecocardiograma de esforço. Avaliámos, em repouso e no esforço, a velocidade da onda S ventricular direita, a excursão sistólica do plano anular tricúspide, a área de encurtamento fracional do ventrículo direito e o volume sistólico indexado. Analisámos o aumento de cada parâmetro entre repouso e esforço para casos e controlos e comparámos a magnitude de variação com o exercício de cada parâmetro entre casos e controlos. Resultados: Nos casos observámos aumento significativo da onda S (repouso 9,4 ± 3,1; esforço 13,7 ± 4,8 cm/seg [p < 0,05]). Nos controlos ocorreu aumento significativo da onda S (repouso 12,9 ± 2,3; esforço 23,0 ± 7,2 cm/seg [p < 0,005]), da excursão sistólica do plano anular tricúspide (repouso 25,7 ± 2,4; esforço 31,0 ± 3,5 mm [p < 0,05]) e da área de encurtamento fracional (repouso 53,8 ± 14,7%; esforço 64,4 ± 9,9% [p < 0,005]). A magnitude de variação da onda S (casos 4,3 ± 3,3; controlos 10,1 ± 5,5 cm/seg [p < 0,05]), da excursão sistólica do plano anular tricúspide (casos 0,6 ± 2,5; controlos 5,3 ± 3,8 mm [p < 0,05]) e da a área de encurtamento fraccional (casos 0,4 ± 11,8; controlos 10,6 ± 5,9% [p < 0,05]) foi significativamente diferente entre casos e controlos. Conclusões: A onda S, a excursão sistólica do plano anular tricúspide e a área de encurtamento fracional aumentaram significativamente com o esforço nos controlos. A onda S foi o único parâmetro que aumentou significativamente nos casos, embora a magnitude desse aumento seja significativamente menor do que nos controlos. Keywords: Right ventricle, Contractile reserve, Pulmonary hypertension, Exercise echocardiography, Palavras-chave: Ventrículo direito, Reserva contrátil, Hipertensão pulmonar, Ecocardiografia de esforço